Addressing HIV/AIDS challenges in Uganda: does social capital generation by NGOs matter? - Kabeba Muriisa, Roberts (Journal of Social Aspects of HIV/AIDS, 2011)
HIV/AIDS has had devastating impacts in many countries, Uganda in particular. However, Uganda is depicted as one of the most successful countries in fighting HIV/AIDS. Among others, Uganda’s success story is attributed to the open general environment which allows open discussions surrounding HIV/AIDS when other countries such as South Africa and Kenya denied the existence of the disease in their countries. In addition, the success is attributed to the policy which allowed many actors to participate in the fight against the disease. The primary focus of this article is to map the process of social capital generation by NGOs and how social capital benefits enhance mitigation of HIV/AIDS challenges in Uganda. The key to social capital is nurturing relationships. In this regard, HIV/AIDS NGOs play a central role in the way individuals, groups and communities interact, and how various kinds of social relations are forged with people living with HIV/AIDS and especially for those who are HIV infected. NGOs’ success in reducing the number of HIV/AIDS cases in Uganda is based on their abilities to generate social capital. This involves inclusion and building social networks and empowerment at the individual and community levels, and disseminating information to reduce social stigma as well as discrimination. We used a mixed-method strategy to collect data for this study. We used a structured questionnaire having quantitative and qualitative question sets which focused on different social capital measurement indicators. We used observations and in-depth face-to-face interviews. A major finding of the study is that the ways individuals and groups are connected and interact with each other are important mechanisms for alleviating HIV/AIDS challenges in Uganda.
Keywords: Social capital; NGOs